“Repeatability of Regional Pulmonary Functional Metrics of Hyperpolarized (129)Xe Dissolved Phase MRI” - Hahn, Andrew D. (J Magn Reson Imaging, 2019)
BACKGROUND: MRI of hyperpolarized (129)Xenon (HP (129)Xe) is increasingly utilized for investigating pulmonary function. Solubility of HP (129)Xe in lung tissue, blood plasma (Barrier), and red blood cells (RBC), with unique chemical shifts, enables spectroscopic imaging of potential imaging biomarkers of gas exchange and microstructural pulmonary physiology. PURPOSE: Quantifying global average and regional repeatability of Barrier:gas, RBC:gas and RBC:Barrier ratios derived from dissolved-phase (129)Xe imaging and their dependence on inter-visit changes in lung inflation volume. STUDY TYPE: Prospective. POPULATION: 14 healthy volunteers. One subject was unable to complete the study resulting in 13 subjects for analysis (8 female, 5 male, ages 24–69, 53.8±13.9). FIELD STRENGTH: 1.5 Tesla. ASSESSMENT: Subjects were imaged using a 3D radial 1-point Dixon method to separate Barrier and RBC component signals, at 2 different time points, with approximately 1 month between visits. RBC:Gas, Barrier:Gas and RBC:Barrier measures were compared across time and with pulmonary function tests (PFTs). STATISTICAL TESTS: Repeatablilty was quantified using Bland Atlman plots, coefficient of repeatability, coefficient of variation (CV) and intra-class correlation coefficients (ICC). Dependence of imaging measures on PFTs and lung volume was evaluated using Spearman and Pearson correlation coefficients, respectively. Statistical significance was determined by F-test for intra-class correlations, and t-test for Spearman correlations and regression. RESULTS: Mean RBC:Gas, Barrier:Gas and RBC:Barrier had CVs of 19.2%, 20.0% and 11.5%, respectively, and had significant ICCs, equal to 0.78, 0.79 and 0.92, respectively. Inter-visit differences in RBC:Barrier were significantly correlated with inter-visit differences in DLCO (r=0.93,P=0.007). Significant correlations with inter-visit lung volume differences and inter-visit differences in mean RBC:Gas (r=−0.73,P=0.005) and Barrier:Gas (r=−0.69,P=0.009) were found. DATA CONCLUSION: Three commonly used (129)Xe MRI based measures of gas-exchange show good repeatability, particularly Barrier:RBC ratio which did not depend on lung inflation volume and was strongly associated with inter-visit changes in DLCO.